Evaluasi Kurikulum Qawa’id dengan Model CIPP di Madrasah Diniyyah Salafiyyah 4 Al-Munawwir Krapyak - Ni'mah, Izzah Naelun; Zamzami, Muhammad Iqbal; Nasiruddin, Nasiruddin; Uzza, Hamzah Usaid (STAI Auliaurrasyidin Tembilahan, 2023)
Madrasah Diniyyah Salafiyyah 4 is an educational institution whose curriculum contains many programs that support Qawa'id mastery. This study uses a qualitative approach and is a type of evaluation research using the CIPP (Context, Input, Process, and Product) evaluation model by Stufflebeam. This study aims to determine the planning, implementation, and evaluation of the Qawa'id curriculum in Madrasah Diniyyah Salafiyyah 4. In general, the management and organization of Madrasah Diniyyah Salafiyyah 4 has been made and implemented very well, but the results of the research show that the procedure for accepting non-student students mukim which is still unclear, there are several inadequate classes, teachers who do not make lesson plans independently, grade level is not yet high, students are not active enough, use of technology as a support for learning. The development and implementation of the curriculum has been very well designed and neatly structured, but there are several things that need to be evaluated, namely the involvement of students in passive learning and the use of media sources.